Visualizing Urban and Demographic Data in R with ggplot2 - Mayor, Igor Sosa; Siddiqui, Nabeel (The programming historian, 2025)
This lesson demonstrates how to use R's ggplot2 package to create sophisticated data visualizations through a 'grammar of graphics' framework. Using historical data about European sister-city relationships in the post-second world war period, including partnerships, population sizes, and geographic distances, the lesson guides readers through the process of creating various plots while exploring urban and demographic patterns.